Biohydrogen production via biocatalyzed electrolysis in acetate-fed bioelectrochemical cells and microbial community analysis - Chae, K.J.; Choi, M.J.; Lee, J.; Ajayi, F.F.; Kim, S.
Hydrogen was efficiently produced via acetate oxidation using a two-chambered bioelectrochemical cell (BEC), a modified microbial fuel cell (MFC), in which a cathode was kept free of oxygen and the thermodynamic barrier overcome by augmenting the electrochemical potential achieved by bacteria with the addition of a small external voltage. The production of hydrogen gradually increased with increasing applied voltage from 0.1 to 1.0 V, reaching its maximum efficiency of 52.5
Keywords: BACTERIAL COMMUNITY; BIOCATALYZED ELECTROLYSIS; HYDROGEN; MICROBIAL FUEL CELLS